Personalized 3D-Printed Bioresorbable Airway External Splint for Tracheomalacia Combined With Congenital Heart Disease - Yu, Di; Peng, Wei; Mo, Xuming; Zhang, Yuxi; Zhang, Xing; He, Jiankang (Frontiers in Bioengineering and Biotechnology, 2022)
Severe tracheomalacia (TM) patients with respiratory symptoms need surgical intervention, including aortopexy, internal stents or external splint. While some patients continue to have respiratory symptoms after tracheal relief, and there is no evidence to support any one surgery therapy over another. Here we introduce a clinical safety and efficacy of the three-dimensional (3D)-printed bioresorbable airway external splints in treating congenital heart disease (CHD) patients with severe TM. From May 2019 to September 2020, nine patients with severe TM were enrolled. The median age was 5 months (range, 3 months to 25 months), and the median weight was 7.5 kg (range, 3 kg to 15 kg). All patients had wheezing, and two patients were assisted by machine ventilation (MV) preoperatively. The median length of TM was 1.5 cm (range, 1.0 cm to 3.0 cm). All patients underwent suspension of a “C”-shaped lumen airway external splint, which were designed in SOLIDWORKS and made of polycaprolactone (PCL). The airway external splint could provided effective support for at least 6 months and was completely degraded into carbon dioxide and water within 2-3 years. The median time of postoperative machine assisted ventilation was 23.7 hours (range, 3.3 hours to 223.4 hours), and the median time of ICU stay was 9 days (range, 4 days to 25 days). The median follow-up time was 18 months (range, 12 months to 24 months). Respiratory symptoms were all relieved, and no external splint-associated complications occurred. The 3D computed tomography reconstruction showed no airway stenosis. Personalized 3D-printed bioresorbable airway external splint can not only limit external compression and prevent airway collapse but also ensure the growth potential of the airway, which is a safe, reliable and effective treatment for CHD with TM.